The use of electronical devices and relative levels of Nomophobia within a group of Italian nurses: an Observational Study (Epidemiology, Biostatistics, and Public Health, 2022)
Background: In healthcare, the use of smartphones and other electronical devices are becoming important tools among health professionals. Thanks to these devices, there are new methods of assistance. However, if used incorrectly, they may cause distraction during clinical practice. The excessive use of such devices has generated a new form of addiction in the workplace named nomophobia, a phobia still little explored in literature. We reported an analysis of the frequency and method of use of these electronical devices. The primary aim of the research was to investigate the level of dependence on electronic devices (nomophobia) and the digital habits of nurses. Secondary aim of the study was to evaluate the possible association between nomophobia and distraction in the workplace.Methods: A transversal multicenter study was conducted on a sample of Italian nurses, using the Nurses’ Use of Personal Communication Devices Questionnaire and the Nomophobia Questionnaire (NMP-Q).Results: 34.1% of the sample (n=184) declared that they used smartphones and other electronical devices a moderately during working hours. 20.2 % (n=109) used them frequently and 8.9% (n=48) uses devices during working hours constantly. However, 44.0% (n=222) never uses health apps for patient medical assistance, the 32.9% (n=166) never uses learning apps or apps for professional development. 16.6% (n=87) admit that the use of these devices negatively affected their working performance (mean 80.5; SD 40.1). Study participants showed moderated levels of nomophobia (media=50.34; SD=29.0).Conclusion: The results of the study demonstrate the scares use of such electronical tools to implement adequate care among Italian nurses. Nomophobia can have significant impact on the risk of making mistakes. Future studies should examine not only nurses but also other help professionals and support staff, to bring out an underestimated dimension.